Creating Web Pages All-in-One Desk Reference for Dummies 2nd Edition - Veer, Emily A. Vander (Wiley Publishing, 2011)
hether you want to build a Web page to recap a recent family reunion, promote your beagle breeding business, or market the next pet rock and make millions through e-commerce, this book will get you started. With almost 800 information-packed pages, it’s actually nine concise minibooks, each tackling a specific aspect of Web development. Beginners will get off to a good start and old hands will learn the latest on XML, JavaScript, and more.